2016
DOI: 10.1016/j.bjane.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Two-year experience with cell salvage in total hip arthroplasty

Abstract: Cell salvage is an effective strategy for reducing the need for allogeneic blood transfusion in the perioperative setting; it provides support to patient blood management interventions. Thus, we recommend the cell salvage system for use in total hip arthroplasty surgeries to reduce the need for allogeneic blood transfusion, if possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…In general, the results of the present study did not reveal a significant reduction in the total volume transfused in the SC group. The mean recovered volume was 335 mL, consistent with authors such as Leigheb et al, 4 Hawi et al 15 and Buget et al, 16 who also showed similar perioperative transfused blood volumes in both groups (average volume at SC Group, 170.14 mL, average volume at control group, 92.53 mL), but this difference between groups was significant, perhaps due to the larger sample (143 patients).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In general, the results of the present study did not reveal a significant reduction in the total volume transfused in the SC group. The mean recovered volume was 335 mL, consistent with authors such as Leigheb et al, 4 Hawi et al 15 and Buget et al, 16 who also showed similar perioperative transfused blood volumes in both groups (average volume at SC Group, 170.14 mL, average volume at control group, 92.53 mL), but this difference between groups was significant, perhaps due to the larger sample (143 patients).…”
Section: Discussionsupporting
confidence: 84%
“…Em geral, os resultados do presente estudo não revelaram uma redução significativa no volume total transfundido no grupo que utilizou o aparelho. A média de volume recuperado foi de 335 mL, compatível com autores como Leigheb et al, 4 Hawi et al 15 e Buget et al, 16 que também mostraram volumes sanguíneos transfundidos no perioperatório nos dois grupos semelhantes ao nosso ensaio (grupo RIOS: média 170,14 mL; grupo controle: média 92,53 mL), porém tal diferença entre os grupo foi significante, talvez pela maior amostra (143 pacientes).…”
Section: Discussionunclassified
“…Preoperative and/or postoperative anemia is associated with significant adverse clinical outcomes, such as an increased frequency of allogeneic transfusion, 4 decreased physical function, [5][6][7] higher infection rate 3 , longer hospital stay, 4, 7-9 and increased mortality. [7][8][9][10] Accordingly, strategies to minimize anemia such as improvement of the serum iron level, preoperative autologous blood donation, [11][12][13][14] intraoperative and/or postoperative blood salvage, [15][16][17] and allogeneic blood transfusion should be considered for patients undergoing elective surgery. However, some studies [18][19][20] have shown that allogeneic blood transfusion is a significant risk factor for surgicalsite infections after orthopedic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Cell salvage (CS) is the intraoperative collection and reinfusion of autologous blood. The main goal of using this system is to reduce the need for ABT and related complications (10). The use of a CS system in orthopedic surgery can restore up to 70% of the intraoperative blood loss and significantly reduce the need for ABT (11).…”
Section: Introductionmentioning
confidence: 99%